To assess the prevalence of smoking & alcohol consumption among health professionals in health institutions of Biratnagar. - Aryal, Kimu (2008)
ABSTRACT: OBJECTIVE: "To Assess the Smoking & Alcohol Consumption among Health Professionals in Health Institutions of Biratnagar". RESEARCH QUESTIONS: "What is the dependency of smoking & alcohol use among HP?" METHODS: Descriptive and Cross-sectional quantitative survey research using stratified random sampling design to examine the cigarette and alcohol use among HP. Hundred and seventeen HP was assessed by a confidential questionnaire, which was distributed, completed by the HP and collected them later on. RESULTS: Of the 128 Hp who responded to the survey. 11 of them did not answer the question due to leave, so were excluded from the sample. Of the remaining 117, 67 (57.3%) were men and 50 (42.7%) were women. On an average age of the respondents was 40.2% (15-25 Years) and 38.5% of them were of 25-35 Years, prevalence of smoking among HP overall was 32.47% where as prevalence of alcohol consumption was 52.13%. In case of regular smoker and drinker, prevalence was much higher among doctor as a regular smoker was 26.83% as well as regular drinker was 12.95%, prevalence of regular smoking among paramedical professional was 22.22% and among nurses was only 5% which was much lower in comparison to doctor and paramedical professional but as a regular drinker none of nurses and paramedical professional were found. Prevalence of doctor towards smoking habit and alcohol consumption as an occasional smoker and drinker is also very high and which was 19.51% and 65.85% respectively, after doctor paramedical professional have high prevalence of smoking and alcohol consumption, which was 19.44% and 52.78% respectively in comparison to nurses who were only 5% occasional smoker and only 25% occasional drinker. The large majority of the smokers and drinkers were between 25 and 35 years old. In the survey, male HP as smokers and drinkers where higher than that of female HP. In terms of when the smokers and drinkers began smoking and drinking, 15.4% of the HP started smoking at the age of 15-25 years old where as 2.6% of HP started drinking at the age of above 25 years old. 6.8% of the HP had quit smoking and 6% of them said that they had quit drinking alcohol. In the survey, 59.8% were non-smokers and 41% of them where non-drinker. CONCLUSIONS: It is indeed a shocking reality that health professional who assume the responsibility of curative as well as preventive medicine are themselves a largest group of victims to the habit of smoking and drinking alcohol. Despite the widespread knowledge that smoking and drinking alcohol causes death and debilitating disease, the prevalence of smoking and alcohol consumption is still higher among HPs.